Europe’s fourfold union: updating the 2012 vision - Véron, Nicolas (Brussels, 2017)
"The depiction of the euro area/European Union (EU) as a ‘fourfold union’ (financial union, fiscal union, economic union, political union) emerged in the first half of 2012 at the height of the euro-area crisis. It was primarily shaped by the recognition of the bank-sovereign vicious circle and the need to break it to ensure the survival of Economic and Monetary Union (EMU).